Pengaruh Pajak Daerah, Retribusi Daerah Dan Laba Badan Usaha Milik Daerah (BUMD) Terhadap Kinerja Pelayanan Publik Daerah Kabupaten Sumbawa - Rusdi (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2025)
This study aims to examine the Influence of Regional Taxes, Regional Levies, and Profits of Regionally Owned Enterprises (BUMD) on Public Service Performance. The population of this study is data on budget realization reports for the last 9 years within the scope of the Government on Sumbawa Island. This study uses all populations as a sample, as many as 5 districts and cities on Sumbawa Island with 45 realization budget report data. The method used in this study is multiple linear analysis with the help of the SPSS version 20. This type of research is associative research with a quantitative approach. The variables in this study are Regional Tax, Regional Levy, BUMD Profit and Public Service Performance and the data used is secondary data. The results of this study show that regional taxes do not have a positive and significant effect on Public Service Performance, regional levies have a positive and significant effect on Public Service Performance, while BUMD profits have a very positive and significant effect on Public Service Performance.